Tracing anthropogenic cadmium emissions: From sources to pollution - Yuan, Zengwei; Luo, Tao; Liu, Xuewei; Hua, Hui; Zhuang, Yujie; Zhang, Xuehua; Zhang, Ling; Zhang, You; Xu, Weiwei; Ren, Jinghua (The Science of the total environment, 2019)
Cadmium (Cd), a widely concerned heavy metal, is toxic to humans and ecosystems. In this paper, a Cd-polluted town in southeast China was selected to estimate the Cd emissions of human activities into surface water, soil and atmospheric environment. The analysis shows that the total amount of Cd emitted into the environment in 2015 was approximately 43.5 kg, and the majority of those emissions were discharged into the water, accounting for approximately 90.4% of the total Cd emissions. The remaining Cd emissions into the soil and atmosphere accounted for 9.5% and 0.1%, respectively. The industrial production (IP) is the dominant source of anthropogenic Cd emissions, which contributes to 62.1% of the total emissions. The other contributors include aquaculture (AQ), wastewater treatment (WT), living consumption (LC), crop farming (CF) and animal breeding (AB); each accounted for less than 10% of the total emissions. Pigment production is the largest source of IP emissions. According to the results of correlation analysis, the pigment enterprises are responsible for the heavy Cd pollution in local soil. By comparing the spatial position and combing with the local watercourses, the study reveals that the irrigated watercourse is the transmission channels of soil Cd pollution. This study contributes to the analysis of connecting the emission inventory, environmental media and transmission channels of the heavy metal Cd and provides policy supports for the local governments to adopt a life cycle Cd management approach. [Display omitted] •A Cd emission inventory was established for Dingshu in 2015.•Industrial production is the main source of environmental Cd.•Pigment enterprises should be responsible for soil pollution.•The irrigated watercourses are the transmission channel for soil Cd pollution.